Pengaruh Kepuasan Kerja dan Kontrak Psikologis Terhadap Intention To Quit dengan Komitmen Organisasi Sebagai Variabel Intervening (Studi Pada Pt. Krakatau Steel, Tbk) - Fitriyah, Fita; Djastuti, Indi (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2020)
The purpose of this study is to analyze the effect of job satisfaction and psychological contracts on intention to quit with organizational commitment as an intervening variable. The population used in this study are operational employees of PT Krakatau Steel Tbk. who have become permanent employees with a minimum work period of 1 year and a minimum education level of high school and equivalent. The number of samples used in this study were 190 respondents. Data collection using a questionnaire. This study uses structural equation modeling (SEM) analysis with AMOS software as an analysis tool. The results showed that job satisfaction had a negative and significant effect on intention to quit, psychological contracts had a negative and insignificant effect on intention to quit, job satisfaction had a positive and significant effect on organizational commitment, psychological contracts had a positive and significant effect on organizational commitment and organizational commitment had a significant effect on organizational commitment. negative and significant on the intention to quit.